PERILAKU KONSUMEN DALAM PEMBELIAN BERAS ORGANIK PRODUKSI KABUPATEN PRINGSEWU - Arif Setiawan; Wan Abbas Zakaria; Yaktiworo Indriani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The purposes of this research were to analyze the process of consumer’s decision making on organic rice purchasing and dominant component that influenced organic rice purchasing by consumers.  This research was conducted in Pringsewu District by considering that location one of the central productions and the pioneer of organic paddy farming in Lampung Province. The data was collected on June-July 2015 with survey method.  The samples of the research were 60 respondents both men and women that met the criteria such as having experience on buying and consuming organic rice at the last three months.  The data was analyzed usely descriptive analysis and statistic with validity, reliability, and principal component analysis.  The result showed that the process of decision making on organic rice purchasing by consumer was through all of the stage such as introduction needs, information searching, alternative evaluation, purchase decision and post purchase evaluation. There were three dominant components that influenced decision making on organic rice purchasing.  The first component was named habit component, the second component was named as appeal component, and the third component was named flavor component. Key words: consumer behavior, organic rice, principal component analysis, purchase decision